On Construction of Nearly Orthogonal Latin Hypercube Designs - A. Anil Kumar; Baidya Nath Mandal; Rajender Parsad; Sukanta Dash (Journal of the Indian Society of Agricultural Statistics, 2025)
Orthogonal Latin hypercube designs are becoming popular in designing computer experiments. Available literature on construction of orthogonal or nearly orthogonal LHDs has one or more restriction in terms of either runs or factors. In this article, we have proposed a method of construction for obtaining nearly orthogonal Latin hypercube designs capable of accommodating flexible number of runs or factors.